-7b=-6b+9

Simple and best practice solution for -7b=-6b+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7b=-6b+9 equation:


Simplifying
-7b = -6b + 9

Reorder the terms:
-7b = 9 + -6b

Solving
-7b = 9 + -6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6b' to each side of the equation.
-7b + 6b = 9 + -6b + 6b

Combine like terms: -7b + 6b = -1b
-1b = 9 + -6b + 6b

Combine like terms: -6b + 6b = 0
-1b = 9 + 0
-1b = 9

Divide each side by '-1'.
b = -9

Simplifying
b = -9

See similar equations:

| 6.5y-18.66=14.02+8.4y | | 28=(-13)+x | | 5/×=1 | | 17=k/2 | | X+-11=7x+-13 | | 3+7n=87-5n | | 8x10/-5 | | 5(a-6)-3=5-(a+2) | | 17=3x+5+4x-9 | | 18=10y-2 | | 0.11-2.2h=9.61+16.1h-17.3h | | 8*10/-5 | | 8=-5/x-8 | | 20a=280 | | (3x-7)(-x^2-4x+5)=0 | | 5=6x+19 | | -6+12=3x-2(x-7) | | 2/3r | | y+7-4(-3y-1)=3(y-1) | | 2x^2-5x^2-12x+30= | | 3xy^2+6y^2+40xy+80y-28x-56=0 | | -5s=5-4s | | 8=5/x-8 | | 6x-12=18x+6-12x | | -154=-5(8+4x)+x | | (6y-7)=-1 | | 8(1/4x-1/4) | | -82=5x-2 | | -6=-n | | 18q-19=12-18+19q | | 2x-6x-6=90 | | -6=n |

Equations solver categories